NFIA haploinsufficiency: case series and literature review - Gianluca Dini; Alberto Verrotti; Paolo Gorello; Luca Soliani; Luca Soliani; Duccio Maria Cordelli; Duccio Maria Cordelli; Vincenzo Antona; Amedea Mencarelli; Davide Colavito; Paolo Prontera (Frontiers Media S.A., 2023)
BackgroundNFIA-related disorder (OMIM #613735) is an autosomal dominant neurodevelopmental disorder characterized by a variable degree of cognitive impairment and non-specific dysmorphic features. To date, fewer than thirty patients affected by this disorder have been described.MethodsOur study included three children with NFIA haploinsufficiency recruited from three medical genetics centers. Clinical presentations were recorded on a standardized case report form.ResultsAll patients presented a variable degree of intellectual disability. None of the individuals in our cohort had urinary tract malformations. Three novel mutations, c.344G>A, c.261T>G, and c.887_888del are reported here.ConclusionNFIA haploinsufficiency can be suspected through careful observation of specific dysmorphisms, including macrocephaly and craniofacial abnormalities. Instrumental tests such as MRI and renal ultrasound provide further diagnostic clues, while genetic testing can confirm the diagnosis.